PENDAMPINGAN TEKNIS PENCATATAN KEUANGAN DAN LEGALITAS USAHA BAGI USAHA MIKRO PEMULA DI KEPULAUAN RIAU - Al Amany, Sarah Ulfah; Mutia Ulfah; Sri Zuliarni; Rahmat Hidayat; Riza Khusniah; Fuad Arif Rahman; Multhahada Ramadhani Siregar; Aprizal Putra; Syafri Naldi; Alrido Martha Devano; Eddo Nanda Oktarici; Ancala Laras Putri; Himawan Mochtoha (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2025)
Micro, Small and Medium Enterprises (MSMEs) have an essential role in the Indonesian economy, but still face significant challenges in financial management and business legality, especially in the Riau Islands with limited access to training. This community service program aims to provide technical assistance in financial recording and business legality for budding micro businesses in the Riau Islands to create independent and sustainable entrepreneurs. Through the Project-Based Learning (PBL) approach, Batam State Polytechnic students accompany micro business actors in simple financial recording and processing legalities such as Business Identification Number (NIB), Taxpayer Identification Number (NPWP), and halal certification. As a result, 80% of participants succeeded in implementing daily transaction recording and 70% in compiling simple financial reports. In comparison, 75% of participants managed business legality through the Online Single Submission (OSS) platform, which increased access to formal financing. This program also changes the participants' mindset towards more professional business management, although further assistance is needed to ensure consistent implementation. This program has the potential to be replicated in other regions to support more competitive and sustainable empowerment of MSMEs, as well as contribute to local economic growth.